The emergence of collective competence in a Brazilian petrochemical company - Claudia Cristina Bitencourt; Fernanda Bonotto (Management Revue, 2010)
Organizations seek new ways to stimulate collective competences. One possible way this can be done is though self-managing teams. This paper aims to understand the collective competences based on their constitutive elements: interaction, sensemaking and identity. For this study we investigated a Brazilian world-class petrochemical company, recognized by their excellence in working with self-managed teams. Two semi-autonomous teams were studied, distinct in its pattern and performance. The main results point out that the understanding of collective competences is more related to the dynamics and the interaction process itself rather than to the content of this approach and its constitutive elements separately.
Keywords: 650; collective competences; interaction; sensemaking; identity